The costs of early school leaving in Europe - Giorgio Brunello; Maria Paola (IZA Journal of Labor Policy, 2014)
The reduction of early school leaving to less than 10 percent of the relevant population by 2020 is a headline target in the Europe 2020 strategy and one of the five benchmarks of the strategic framework for European cooperation in education and training. Designing adequate policies to combat early school leaving is a difficult task that requires both the identification of causal links and the measurement of costs and benefits. In this paper, we review the issues surrounding the measurement of the costs of early school leaving to individuals and societies and examine several implemented policies that are expected to affect early school leavers. These include broad policies - such as changes in minimum school leaving age, tracking and school resources - as well as more targeted policies. While our focus is mainly on Europe, we also consider important evidence from across the Atlantic.
Keywords: J24; 330; Early school leaving; Europe; Policy evaluation